A contribuição da vitivinicultura na formação de profissionais da gastronomia - Ruffato, Gustavo André (My University, 2025)
The integration between gastronomy and viticulture has gained prominence in Brazilian academia, particularly in Rio Grande do Sul, one of the country's main wine-producing regions. This dissertation analyzed the approach to wine education in the Technology in Gastronomy program at the University of Caxias do Sul, investigating how wine knowledge is incorporated into the curriculum and its influence on professional training. Through documentary analysis and interviews with students, the study evaluated the subjects Viticulture and Enology, and Enogastronomy and Wine Tourism, as well as students' perceptions of the impact of this knowledge on their careers. The results indicate that 87% of respondents recognize that wine education enhances their gastronomic skills, improving their ability to pair food and wine and reinforcing local cultural appreciation. Furthermore, the curriculum was found to promote an integration between regional tradition and academic innovation, aligning with market demands. The study concludes that strengthening viticulture education in gastronomy programs significantly contributes to the training of more qualified professionals, boosting the sector and reinforcing the region's gastronomic identity. [resumo fornecido pelo autor]
A integração entre gastronomia e vitivinicultura tem ganhado destaque nas academias brasileiras, especialmente no Rio Grande do Sul, uma das principais regiões vinícolas do país. Esta dissertação analisa a abordagem do ensino enológico no curso de Tecnologia em Gastronomia da Universidade de Caxias do Sul, investigando como o conhecimento sobre vinho é incorporado ao currículo e sua influência na formação profissional. Por meio de análise documental e entrevistas com estudantes, foram avaliadas as disciplinas de Viticultura e Enologia e Enogastronomia e Enoturismo, bem como a percepção dos alunos sobre o impacto desse aprendizado em suas carreiras. Os resultados indicam que 87% dos entrevistados confirmaram que o ensino do vinho amplia suas competências gastronômicas, melhorando a capacidade de harmonização e valorização da cultura local. Além disso, constatou-se que o currículo promove uma integração entre tradição regional e inovação acadêmica, alinhando-se às demandas do mercado. O estudo conclui que fortalecer a educação vitivinícola nos cursos de gastronomia contribui significativamente para a formação de profissionais mais fortes, impulsionando o setor e reforçando a identidade gastronômica da região. [resumo fornecido pelo autor]
Keywords: Gastronomia - Estudo e ensino; Vitivinicultura; Formação profissional; Vinho e vinificação; Gastronomy - Study and teaching; Viticulture; Occupational training; Wine and wine making